The Impact of Using Audio Visual Media to Improve Letter Recognition Ability in Kindergarten - Ayuni, Ni Made; Paramita , Made Vina Arie (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Learning currently still uses traditional methods, namely with a whiteboard and markers to introduce letters to children. This study aims to analyze the effect of audio-visual media on the letter recognition skills of children aged 4 to 5 years in kindergarten. This research is included in the type of quantitative experimental research that uses Quasi Experimental Design with Non Equivalent Control Group Design. The population of this study consisted of 30 kindergarten children. Because the population size was less than 100, complete sampling was used to guarantee the sample. Research data collection was carried out using the structural observation method. Meanwhile, data analysis was carried out using descriptive statistical techniques. Analysis of post-test data shows that there is a significant influence of audio-visual media on children's ability to recognize letters. This can be seen from the significant increase in their average performance, which increased from 27.73 before the intervention to 54.93 after the intervention. The results of the hypothesis test further support this observation, because the significance value of 0.002 is lower than the threshold set at 0.05. Therefore, it can be concluded that there is a statistically significant average difference in students' letter recognition skills between the experimental group and the control group. The latest information in this research can have implications for the continued application of audio-visual media to improve the ability to recognize letters in kindergarten children.